Transtendon rotator-cuff repair of partial-thickness articular surface tears can lead to medial rotator-cuff failure - Woods, Tom C (Dove Medical Press, 2014)
PURPOSE: The purpose of this study was to evaluate clinical and anatomic outcomes of patients following transtendon rotator-cuff repair of partial articular supraspinatus tendon avulsion (PASTA) lesions. PATIENTS AND METHODS: Patients in the senior author’s practice who had isolated PASTA lesions treated by transtendon rotator-cuff repair were included (n=8) and retrospectively reviewed. All patients were evaluated preoperatively and at a mean of 21.2 months (±9.7 months) postoperatively using standardized clinical evaluation (physical exam, American Shoulder and Elbow Surgeons, and Simple Shoulder Test). All patients underwent postoperative imaging with a magnetic resonance imaging arthrogram. RESULTS: There was a significant improvement in American Shoulder and Elbow Surgeons (42.7±17.5 to 86.9±25.2) and Simple Shoulder Test (4.6±3.2 to 10.1±3.8) scores from pre- to postoperative, respectively. Postoperative imaging demonstrated full-thickness medial cuff tearing in seven patients, and one patient with a persistent partial articular surface defect. CONCLUSION: Transtendon repair of PASTA lesions may lead to improvements in clinical outcome. However, postoperative imaging demonstrated a high incidence of full-thickness rotator-cuff defects following repair.